Տիգրան Մեծը հռոմեացի պատմիչների տեսանկյունից - Մարտիրոսյան, Մադոնա («Զանգակ - 97»)
The 90-70s of the first century are special in the history of the Armenian people. At that time, Armenia took the path of foreign conquests, creating a world power in Near East. And that happened during the reign of Tigran the Great (95-55 BC). We have tried to present the information provided by two authors with the help of historical-analytical method. Cicero, as mentioned, was a member of the Roman Senate during the reign of Tigran the Great, and his opinions were particularly formed on the basis of the reports received by the Senate. And Plutarch is a historian of the Tigranian period, and he probably repeated the information before him, adding more richness to it. In order to demonstrate the power of the Roman generals, these historians tried to belittle the real power of Tigran the Great in front of their own people and history. The most vivid example is the description of the scene of the seeming bowing of the Armenian king Tigran the Great to Pompey in Plutarch's book, which was later repeated regularly by different authors, each time presented with more epic splendor. This episode, we believe, is not true. Meanwhile, the Triumvirate of Rome was busy looking for new leaders of the country, and Pompey was in a hurry to reach Rome and easily agreed to conclude a peace act on the terms proposed by Tigran the Great, in return for which Tigran the Great gave him 6000 talents of gold and silver from the treasury of Tsopk. Roman historians favored the fictionalization of this episode by portraying the father instead of the son. We are sure that the Roman general would have taken Tigran the Great as a show of triumph if the Armenian king had been imprudent and mistakenly actually ended up in Pompey's garrison. But since Tigran the Great did not personally go to the Roman's military base, the latter took his son, Tigran the Younger, as a pilgrim to Rome, when before that he had signed an alliance of brotherhood with Tigran the Great.
Keywords: Հայոց պատմություն